Service levels of highway toll plazas: the influence of factors on manual customer service - Lima,Josiane Palma (2019)
Abstract Paper aims To analyze service levels offered in a highway toll plaza and to test the influence of operational and human factors on manual customer service. Originality The methodology is an approach which involves systematic and efficient examination of multiple factors. This approach has been widely used in multiple areas; however, little research has been done on experiments in the area of transportation. Research method Design of Experiment (DOE) and Computation Modeling and Simulation. Main findings The association of the two methods allowed the development of a more robust empirical model of the customer service process. We have also verified that the human agent interacts and interferes in the manual payment process. Implications for theory and practice To contribute to the very important debate that surrounds service processes. The research showed that there are alternatives and improvements that can be applied and to serve as basis for transportation policies.